(untitled) (Revista Contexto & Educação, 2020)
This paper presents the excerpt of the empirical material collected in an investigation, conducted from 2014 to 2018, whose subjects are teachers of Science and Mathematics and Informatics areas of the integrated technical course of Maintenance and Support in Informatics, in the modality of Youth and Adult Education. The text analyzes the teachers’ own perceptions about the teaching work done in the course, highlighting, among other aspects, the materialization of the integrated curriculum through the so-called Integrator Projects. Through the qualitative approach, as a case study, interviews were conducted inspired by the comprehensive method, as a means of achieving the perception that the subjects have of their work. The theoretical framework is based on authors of the Historical-Critical Pedagogy and Teaching Knowledge. Among the results obtained, we highlight in this text how the subjects perceive the materialization of the integrated curriculum. By analyzing the content of the interviews, advances and possibilities are identified in the foundation of the Integrating Projects, taking into account the complex and real context.